(untitled) (Research, Society and Development, 2023)
Objective: To analyze data related to Spinal Disc Disorders (SDD) in Brazil between 2013 and 2023, obtained from the Unified Health System Hospital Information System (SIH/SUS). Methodology: This is an ecological, descriptive, and retrospective study of hospitalizations due to SDD in Brazil. Results: During the analyzed period, 139,447 hospitalizations were registered. Of these, 54.6% of the patients were male, 53% were treated in the emergency service, the most affected age group was adults, with an incidence of 6.8 cases per 10,000 inhabitants, a mortality rate of 0.71%, and approximately 2 individuals being hospitalized every hour due to the disease. Conclusion: The regional and national incidence remained constant over the 10 years, with an average cost of R 5,473.39 per hospitalization and an average length of hospital stay of 6.9 days per person. Men are more affected than women, and the age group between 40 and 59 is the most vulnerable, which aligns with existing literature on issues related to work hours, duration of economic activity, and physical workload. Given the significant impact of SDD on public health and the economy, it is imperative to adopt new healthcare policies and conduct further studies to provide proper guidance for the prevention of this group of disorders, especially for the analyzed population.